Language communication skills and school crisis from the perspective of the public schools principals in Kuwait / Fahad Mayouf K Al Anazi - Fahad Mayouf K , Al Anazi (2019)
This study aimed at looking into the most important language communication skills in the Arabic language (verbal and non-verbal) and identifies the most prominent school crisis that public schools in Kuwait face from the response of the sample of the study. The study also identifies differences among individuals of the sample in their views of the most important language communication skills in the Arabic language (verbal and non-verbal) as well as their views on the most prominent school crisis in the perspective of the principals of public schools according to the variables of the study (gender, educational zone, academic qualification, years of service in school administration) and to identify the possibility of a relationship between language communication skills and school crisis. The study’s population is made up of principals of public schools in Kuwait (primary, middle school and secondary school) for the 2015/2016 academic year. The total population is 592 male and female principals out of which 263 male and female were sampled out using simple random sampling. The study tool (questionnaire) was built after reviewing the theoretical side, previous studies and theories, and the models associated with each axis of the tool axes. This is done to identify the terms of each axis of the study and to formulate its paragraphs. The sections of the study instrument were formulated and two different questionnaires were used as the tool of the study. The first questionnaire is to measure language communication skills (verbal and non-verbal) among Kuwaiti principals of public schools. The second questionnaire is to measure schools’ crisis (students and teachers’ crises) from the views of the schools’ directors. The study has made several findings, the major ones are: that the degree of language communication skills (verbal) among Kuwaiti principals of public schools is moderate. The aspects are ranked as follows: listening, speaking, reading, and writing. On the other hand, the degree of the linguistic communication skills (nonverbal) among Kuwaiti principals of public schools is also moderate. The aspects are ranked as follows: Proxemics and chronemics, body movements, physical appearance and the voice. Whereby the degree of the most prominent school crisis based on the public schools’ principals’ opinions is also moderate. The degree came in the following order: students’ crisis and then teachers’ crisis. The study found that there are statistically significant differences in the opinions of the sample of the study on the most important language communication skills (verbal and nonverbal) according to the gender variable and in the verbal communication according to the educational zone but no significant differences found in other variables. Likewise, there are statistically significant differences in the opinions of the sample of the study on the most prominent school crises according to the gender variable only. Also, there is an existing relationship of a positive statistical significance at the level (α≤0.05) between language communication skills and schools’ crisis in Kuwaiti public schools. One of the most distinguished feature of the study is its conclusion that positive language communication is important in the mitigation of school crises The study recommends raising the degree of language communication skills (verbal and nonverbal) among the Kuwaiti principals of public schools as well as appointing principals that are skillful in dealing with schools’ crisis, and training them in the art of dealing with school crisis.